Implementation of Fun Learning in Increasing Children's Interest in Learning in Ciririp Village through the Community Service Program - Ilah Nursolihah Nugraha; Enan Kusnandar; Usep Setiawan (Yayasan Daarul Huda Kruengmane, 2026)
This community service activity aims to implement the Fun Learning model based on Participatory Action Research (PAR) to increase children's interest in learning in Ciririp Village, Purwakarta Regency. The approach used is descriptive qualitative with a PAR cycle that includes planning, action, observation, and reflection. The subjects of the activity were 14 elementary school-aged children who participated in a non-formal learning program based on educational games, interactive quizzes, and creative activities. The results of the activity showed positive changes in learning interaction patterns, increased courage among children to participate, and the growth of intrinsic motivation during the learning process. Theoretically, these findings are in line with social constructivism, experiential learning, and Self-Determination Theory, which emphasize the importance of direct experience and social interaction in learning. This PAR-based Fun Learning model has the potential to become an alternative to socio-cultural engineering in building a participatory and contextual learning culture in the community.